2021
DOI: 10.1111/famp.12714
|View full text |Cite
|
Sign up to set email alerts
|

Family profiles based on family life satisfaction in dual‐earner households with adolescent children in Chile

Abstract: Research has stressed the importance of the family domain for the individual's well‐being, but the heterogeneity/homogeneity of satisfaction with family life between and within families have not previously assessed. This study identifies family profiles based on the level of family life satisfaction in mother–father–adolescent triads and determines whether profiles differ in terms of the three family members’ perceived family support, importance assigned to the family, both parents’ work–life balance and menta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 69 publications
2
2
0
Order By: Relevance
“…At the same time, the three-class multiple comparison analysis further verified the difference rule. This classification supports studies showing that satisfaction in good life domains varies between rural households [49]. Specifically, 9.6% of households belong to the very-satisfied class, which has high satisfaction in industrial economy, living environment, rural culture, rural governance, and material life.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…At the same time, the three-class multiple comparison analysis further verified the difference rule. This classification supports studies showing that satisfaction in good life domains varies between rural households [49]. Specifically, 9.6% of households belong to the very-satisfied class, which has high satisfaction in industrial economy, living environment, rural culture, rural governance, and material life.…”
Section: Discussionsupporting
confidence: 85%
“…Higher education level is an individual factor that can significantly improve satisfaction with a good life [60,61]. Previous research has demonstrated that households with highquality employment or higher monthly income show higher life satisfaction [49,62]. The conclusions of this study support this view that providing farmers with more quality and efficient off-farm livelihood strategies to increase their household income can significantly improve their satisfaction with a good life.…”
Section: Discussionsupporting
confidence: 74%
“…Schmidt and Padilla (2003) found that family encouragement helped young people develop confidence and positive self-images. Current studies also report the crucial role of the family in life satisfaction in young people (Orellana et al, 2022). Reports show that family problems affect life satisfaction, and additionally, in academic settings, family problems affect life satisfaction (Mei et al, 2022).…”
Section: Discussionmentioning
confidence: 72%
“…Different studies have reported that SWL and SWFoL are heterogenous in adults [ 15 , 16 , 17 ] and adolescents [ 17 , 18 , 19 , 20 ], which has been linked to different eating behaviors, nutritional states and sociodemographic characteristics. Although there are studies that have addressed the identification of profiles based on parental feeding practices, family eating habits, satisfaction with family life, satisfaction with life, and others [ 21 , 22 , 23 , 24 ], there is still a paucity of studies that have focused on identifying profiles on the basis of SWFoL in the different members of family groups, and distinguishing the differences in their eating habits, bearing in mind the heterogeneity that exists in SWFoL, an aspect to which the present study endeavors to contribute.…”
Section: Introductionmentioning
confidence: 99%